Generalizing of the EDIT model for non-tourism domains - Brehm, Lars (Academica turistica, 2017)
Integrating design aspects into the developing process of new services is a growing trend. One such attempt has resulted in the experience design, innovation, and touchpoints model, known as the edit model designed for the introduction of tourism (re-)innovations (Zach & Krizaj, 2016). The edit model employs design thinking and an innovation adoption process approach. In this paper, how the edit model can be applied to and adopted for other domains is investigated. The structure and method of this presented research note is the following. The existent edit model and its relevance in tourism are presented. Next, all three of the model's axes are analysed for its usage in general business domains in the form of updated EDIT* model. According to the findings, two research & development EDIT* strategies are presented with relevant cases. This paper ends with conclusions, future research, together with identified EDIT*'s weaknesses and strengths.
Keywords: inovacije; modeli; razvoj; storitve